Smart Material for Energy Harvesting and Energy Storage in Mechanical Systems - Mukesh Ganchi (International Journal of Energy and Thermal Applications, 2024)
The integration of smart materials into mechanical systems for energy harvesting and storage marks a transformative leap in sustainable energy technology. These materials, responsive to environmental cues, offer innovative solutions for capturing energy from mechanical sources. Leveraging properties like piezoelectricity and thermoelectricity, smart materials efficiently convert mechanical energy into electrical energy, enabling devices to generate power from human motion or industrial machinery. Moreover, they enhance energy storage capacity and efficiency in batteries and capacitors, while their dynamic nature enables the creation of self-regulating systems adaptable to changing energy demands and environmental conditions. Despite their promise, challenges such as scalability and manufacturing costs require addressing to fully realize their potential in mechanical energy systems.
Keywords: Energy harvesting; Energy storage; Mechanical systems; Renewable energy; Smart materials; Sustainability